If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2z/3-3/2=3z/2-17/3
We simplify the equation to the form, which is simple to understand
2z/3-3/2=3z/2-17/3
Simplifying:
+ 0.666666666667z-3/2=3z/2-17/3
Simplifying:
+ 0.666666666667z-1.5=3z/2-17/3
Simplifying:
+ 0.666666666667z-1.5=+1.5z-17/3
Simplifying:
+ 0.666666666667z-1.5=+1.5z-5.66666666667
We move all terms containing z to the left and all other terms to the right.
+ 0.666666666667z-1.5z=-5.66666666667+1.5
We simplify left and right side of the equation.
-0.833333333333z=-4.16666666667
We divide both sides of the equation by -0.833333333333 to get z.
z=5
| x^2-11x+26=8 | | 36+48x+16x^2=0 | | -2(p-5)+7p=-6 | | -7f=72-f | | 2n+8=2-6 | | -15x+5x^2=0 | | 8(7x-3)=24x | | (10x+10−x)/(10x−10−x)=5 | | 13(x-2)=8x+4 | | 4x+8=15x-25 | | [3x]+8=9 | | 2z+32=126 | | 4-15u=4u^2 | | z+(z+32)=126 | | 4[2x-3]=28 | | 5(7x-6)=35x+4 | | n/8-12=-1 | | 11x-24=-11 | | 17a+26=-42 | | 5x+25/6= | | .40x+.05(6-x)=.10(-60) | | .125m=125 | | 4y=x^2-4 | | H=78+30t+-16t^2 | | 4a-ab=a | | (5x-7)(2x+1)=10x(x-4) | | -8x^2+46x-30=17 | | 6x-2x+8=+5+8 | | 8x-x^2=24 | | 16(x+3)=7(x-5)-9(x+4)-7 | | 6x^2-48x=36 | | 11a^3-11a= |